The Discovery (and Rediscovery) of a Temple Dedication to Hercules by P. Aelius Hieron, Freedman of Hadrian (AE 1907, 125) - Brennan, T. Corey (Hyperboreus, 2017)
This study republishes an inscribed architrave/frieze (AE 1907, 125) from a small temple to Hercules that P. Aelius Hieron, freedman and ab admissione (head of presentations) of Hadrian, set up at in his villa in the ager Nomentanus near modern Monterotondo. After its discovery in 1906 on the Tor Mancina estate of the Boncompagni Ludovisi, it appears the head of family moved the piece to Rome and incorporated it (by 1926) in a private garden fountain, where it has since escaped scholarly notice. The rediscovery of the architrave/frieze allows resumed speculation about the ﬁnancial means and ideology of its dedicator, who is technically one of the most senior imperial freedmen known from the era of Hadrian (117–138) or his successor Antoninus Pius (138–161).